2023
DOI: 10.1007/s00268-023-07067-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Versus Biological Mesh in Ventral Hernia Repair and Abdominal Wall Reconstruction: A Systematic Review and Recommendations from Evidence‐Based Medicine

Hekai Shi,
Rui Wang,
Wenpei Dong
et al.

Abstract: Aim To compare the efficacy and safety of synthetic and biological meshes in ventral hernia repair (VHR) and abdominal wall reconstruction (AWR). Methods We screened all clinical trials that reported the application of synthetic and biological meshes in VHR and AWR using Medline, Web of Science, and Embase (Ovid). Only comparative studies with similar baselines such as age, sex, body mass index, degree of wound contamination, and hernia defects between the intervention and control groups were included. Effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Despite concerns with synthetic mesh, Rosen et al 11 have successfully demonstrated that it can be considered in contaminated VHR when placed in the retromuscular position with superior outcomes to biologic mesh. Other studies reflect this shift toward using synthetic mesh in certain contaminated environments 29,32–34 . Our results demonstrate that the use of biosynthetic mesh shows similar outcomes to synthetic mesh, making P4HB a viable option for surgeons due to its relatively low infection rates and sustained QoL improvement.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Despite concerns with synthetic mesh, Rosen et al 11 have successfully demonstrated that it can be considered in contaminated VHR when placed in the retromuscular position with superior outcomes to biologic mesh. Other studies reflect this shift toward using synthetic mesh in certain contaminated environments 29,32–34 . Our results demonstrate that the use of biosynthetic mesh shows similar outcomes to synthetic mesh, making P4HB a viable option for surgeons due to its relatively low infection rates and sustained QoL improvement.…”
Section: Discussionsupporting
confidence: 58%
“…The concern of infection due to contamination has led surgeons to avoid permanent synthetic mesh. Some recent studies continue to affirm an increased risk of infection and complications when using synthetic mesh 29 . However, biologic mesh has unacceptable rates of recurrence and complication despite its high cost 17,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Stronger repair may have been achieved if direct fixation of the iliac crest was performed at the time of fascial fixation, as these reports 15,16) . Mesh reconstruction is now the gold standard for hernia treatment but often results in recurrent hernias or necessitates additional treatment due to foreign body infection 17,18) . In cases of repetitive recurrence after mesh reconstruction, concomitant infection, and large defects, alternative reconstruction methods include fasciocutaneous flaps, including tensor fascia lata flaps and fascia lata autografts [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports of the effect of decellularized tissue on hydroxyproline and hydroxylysine synthesis during the tissue regeneration process. Injury of a tendon, ligament or fascia, especially in athletes, puts returning to preinjury functionality at risk [ 65 , 66 , 67 ]. The limbs with healed ligaments or tendons achieve lower results and asymmetricity in athletic performance [ 68 , 69 ].…”
Section: Decellularization Methodsmentioning
confidence: 99%